2016
DOI: 10.1210/en.2016-1372
|View full text |Cite
|
Sign up to set email alerts
|

Foxo1 Is Required for Normal Somatotrope Differentiation

Abstract: The etiology for half of congenital hypopituitarism cases is unknown. Our long-term goal is to expand the molecular diagnoses for congenital hypopituitarism by identifying genes that contribute to this condition. We have previously shown that the forkhead box transcription factor, FOXO1, is present in approximately half of somatotropes at embryonic day (e) 18.5, suggesting it may have a role in somatotrope differentiation or function. To elucidate the role of FOXO1 in somatotrope differentiation and function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that mutation of Neurod4 in mice leads to almost completely lack of GHRHR expression and markedly decrease in GH expression 21 , 37 . Mutation of Foxo1 in mice also results in delayed somatotrope differentiation 38 . Notably, we found that NEUROD4 was clearly activated in Pro.PIT1_all cells in comparison with the stem cells (logFC = 1.6, P = 1.3E–18, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that mutation of Neurod4 in mice leads to almost completely lack of GHRHR expression and markedly decrease in GH expression 21 , 37 . Mutation of Foxo1 in mice also results in delayed somatotrope differentiation 38 . Notably, we found that NEUROD4 was clearly activated in Pro.PIT1_all cells in comparison with the stem cells (logFC = 1.6, P = 1.3E–18, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FOXO1 (forkhead box transcription factor 1) plays a role in normal somatotrope differentiation as well as gonadotrope function. However, no role of this transcription factor has yet been described in lactotroph cell or in pituitary tumorigenesis [ 39 ]. That being said, it is worth mentioning that FOXO TFs are well-known targets of AKT1, and important regulators of cell-cycle and proliferation in many cell types.…”
Section: Resultsmentioning
confidence: 99%
“…Among other genes, scRNA-seq shows upregulation of FOXO1 and CEBPD in fetal human somatotrophs [14]. Pituitary-specific double knock-out of FOXO1 in mice results in delayed terminal differentiation of somatotrophs and reduced expression of GHRHR [22]. Additionally, FOXO1 knock-out results in decreased expression of NEU-ROD4.…”
Section: Normal Somatotroph Transcriptional Pathways During and After...mentioning
confidence: 99%
“…Additionally, FOXO1 knock-out results in decreased expression of NEU-ROD4. Thus, FOXO1 may be an upstream regulator of NEUROD4 during somatotroph differentiation [22]. However, this mechanism is still unclear, as scRNA-seq in human fetal somatotrophs suggests that NEUROD4 is upregulated before FOXO1 expression [14].…”
Section: Normal Somatotroph Transcriptional Pathways During and After...mentioning
confidence: 99%